Lowe, Ed., The Vietnam War - Davis, Mark (Teaching History: A Journal of Methods, 2001)
This volume of essays by European, Asian, and American scholars, relying mostly on secondary sources, is an uneven introduction to the level that different nations were involved in the Vietnam War. The consensus that emerges from this global perspective is that the Vietnamese fought the war to preserve their nationalist revolution, while other participants viewed it in light of their larger cold war strategies. These essays all champion Vietnamese nationalism, but criticize foreign and particularly American intervention. Readers looking for a conservative point of view on the war will be disappointed.